The influence of olive orchards copper-based fungicide use, in soils and sediments: the case of Aetoliko (Etoliko) lagoon western Greece - Avramidis, Pavlos; Barouchas, Pantelis; Dünwald, Thomas; Unkel, Ingmar; Panagiotaras, Dionisios (Geosciences, 2019)
In this study, soil and aquatic sediments were sampled in the Aetoliko Lagoon and its catchment area, which is exclusively dominated by olive orchards. For the first time in Greece, soil as well as sediments samples of one coherent protected aquatic ecosystem were directly compared. In order to determine the influence that the usage of copper-based fungicides have on the lagoon sediments and on the soils of the surrounding area, twenty five (25) soil samples from different olive orchards that are bordering the water body and ten (10) sediment samples from the bottom of the lagoon were taken. The samples were analyzed for total copper content (total digestion) and extractable copper (diethylenetriaminepenta acetic acid, DTPA, extraction method). Furthermore, soil/sedimentological and geochemical analyses such as pH, grain size, total organic carbon, total sulfur, total nitrogen, and calcium carbonate content were carried out. The results show that the total copper in soils ranges from 58.37 to 671.33 mg kg−1. In addition the DTPA-extractable copper in soils has an average value of 45.00 mg kg−1. The average value of total copper in soils (286.24 mg kg−1) is higher than the threshold value for the Cu concentration (100 mg kg−1) set by the EU countries. Total copper content in the lagoon sediments is lower than in soils and varies between 43.85 mg kg−1 and 71.87 mg kg−1. The DTPA-extractable copper in sediments is in low ranges from 0.14 to 0.60 mg kg−1. On average, the total copper value for the lagoon sediments (55.93 mg kg−1) exceeds the Toxicity Screening Value (25.20 mg kg−1) for Cu in freshwater sediments. From the present study, it is clear that, although the copper in soils of the surrounding lagoon area exceeds the threshold limit for ecological risk, the lagoon sediments are influenced in a smaller degree. Our study can be used as a valuable reference and baseline for future studies on the environmental monitoring of the Aetoliko lagoon, as well as for studies in similar ecosystems.